Managing Status Epilepticus in a Child with Dravet Syndrome: How Difficult It Could Be? - Badv, Reza Shervin; Ghamari, Azin; Ashrafi, Mahmoud Reza; Mohammadi, Mahmoud; Azizi Malamiri, Reza; Heidari, Morteza (Journal of Pediatric Epilepsy, 2021)
Previously known as severe myoclonic epilepsy of infancy, Dravet syndrome is characterized by febrile or afebrile prolonged hemiconvulsive seizures or generalized status epilepticus in an infant with previously normal development. Immediate management of status epilepticus is critical in these patients. Early control of status epilepticus prevents further brain damage; however, there is no consensus regarding the management of status epilepticus in children with Dravet syndrome, as many conventional antiseizure medications that are recommended in the management of status epilepticus worsen the seizures in these patients. A 2.5-year-old girl child patient was referred due to status epilepticus which was refractory to antiseizure medications. Sodium valproate, nitrazepam, ketogenic diet, intravenous phenytoin, and midazolam continuous infusion were administered. After controlling status epilepticus, the probable diagnosis of Dravet syndrome was proposed and confirmed by a mutation in SCN1A. As previously stated in numerous case reports, phenytoin worsens seizures in patients with Dravet syndrome. Therefore, it seems logical that in every infant with status epilepticus and probable Dravet syndrome, the practicing physician considers administering intravenous valproate or even midazolam continuous infusion instead of intravenous phenytoin.
Keywords: status epilepticus; Dravet syndrome; SCN1A